Model development of early breastfeeding initiation and exclusive preparation - Indrasari, Nelly; Mugiati, Mugiati; Octaviana, Amrina; Djayasinga, Rodhiansyah (Intelektual Pustaka Media Utama, 2024)
The research was conducted in June-September 2022. The early breastfeeding initiation rate (EBI) in one of the districts in Indonesia in 2022 will only reach 8.74%, of the target of 42%. This study aimed to increase the percentage of EBI implementation in birthing mothers and the success of EBI in the first 30 minutes of labor through the development of EBI model. The research method uses a quasi-experimental control group design. The population is 96 people. The sample is the total population, consisting of 48 people closest to pregnant women plus 48 people in the control group. The effect of mentoring shows significant results on the success of EBI because of the value of p=0.002. The mother's educational contribution did not affect the success of EBI between the intervention group and the control group (p=0.774). The family support factor resulted in a significant EBI win between the intervention and control groups (p=0.000). The achievement of EBI provision was 100% of the target of 60%, the achievement of EBI>1 hour was 7.2%, and EBI<1 hour was 92.8%.